Non-pharmacological treatments in cancer pain management - Edlin, Edlin; Lina, Juliana; Nazara, Novita Mirna Sari (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Non-pharmacological therapies have recently become the focus of attention in many countries, including pain management in patients with cancer. This study aimed to explore the latest scientific evidence regarding pain management using non-pharmacological therapies in patients with cancer. The method used was a scoping review using the PRISMA-ScR framework. A literature search was conducted using four databases: PubMed, DOAJ, and Google Scholar, and published in the range of 2018-2023. There of 992 potentially relevant articles and 10 eligible articles were selected. The results of the study showed that nonpharmacological therapy was effective in reducing the pain scale in cancer patients based on the significant value and effect size of providing interventions to patients.